2018
DOI: 10.1172/jci.insight.97844
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing IgG distribution to lung mucosal tissue improves protective effect of anti–Pseudomonas aeruginosa antibodies

Abstract: IgG antibodies are abundantly present in the vasculature but to a much lesser extent in mucosal tissues. This contrasts with antibodies of the IgA and IgM isotype that are present at high concentration in mucosal secretions due to active delivery by the polymeric Ig receptor (pIgR). IgG is the preferred isotype for therapeutic mAb development due to its long serum half-life and robust Fc-mediated effector function, and it is utilized to treat a diverse array of diseases with antigen targets located in the vasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 37 publications
(36 reference statements)
1
11
0
Order By: Relevance
“…Moreover, the higher doses of mAbs used in patients (e.g., ∼35 mg/kg for casirivimab and imdevimab [REGN mAbs]) could compensate for loss in neutralization potency. Generally, in mice and hamsters, mAb-mediated protection was better in the lung than in nasal washes, possibly because IgG levels in the respiratory mucosa are lower than in plasma 21,22 .…”
Section: Therapeutic Efficacy Against Variantsmentioning
confidence: 97%
“…Moreover, the higher doses of mAbs used in patients (e.g., ∼35 mg/kg for casirivimab and imdevimab [REGN mAbs]) could compensate for loss in neutralization potency. Generally, in mice and hamsters, mAb-mediated protection was better in the lung than in nasal washes, possibly because IgG levels in the respiratory mucosa are lower than in plasma 21,22 .…”
Section: Therapeutic Efficacy Against Variantsmentioning
confidence: 97%
“…Previous studies have demonstrated that conferring pIgRbinding abilities to IgG and other biologic payloads can result in the transport of such molecules across the epithelial barrier. [15][16][17][18][19][20][21][22][23][24][25] Thus, we sought to generate VHHs that could be transported via pIgR for use as a delivery moiety in multi-specific antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…15,19,23 In the most recent work, an anti-P. aeruginosa IgG fused with pIgR-binding peptides exhibited enhanced localization to the bronchoalveolar space, maintained Fc-mediated functional activity and promoted enhanced survival in an acute pneumonia model. 15 Given that the VHH scaffold is small (12-15 kDa) and wellrecognized for high stability, solubility, cleft recognition properties, low production costs and easy genetic cross-linking, 33,34 we generated VHHs against pIgR to develop a mucosal drug delivery platform. Following llama immunization, B-cell sorting and VHH gene isolation, we expressed, purified and screened a panel of 73 VHH-mFc molecules for binding to mpIgR and hpIgR ECD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, bamlanivimab is an IgG 1 , and these immunoglobulins cannot be secreted to mucosal tissue like IgA and IgM. It has been demonstrated that systemically administered IgG levels in bronchoalveolar lavage (BAL) can be approximately 1,000 times lower than levels of IgG in serum [ 72 ]. Furthermore, the injury of the respiratory tissue by inflammatory processes probably determines a further limitation to bioavailability.…”
Section: Expert Opinionmentioning
confidence: 99%